Physicality in the measurement of the primary caregiver-infant interaction: A descriptive review of global observational assessment tools and coding schemes - Westerdahl, Jacqueline E.; Moerchen, Victoria A. (Neuroscience and biobehavioral reviews, 2025)
Attachment Theory emphasizes the importance of physical contact between primary caregiver and infant to support infant social-emotional development. In stark contrast, caregiver physical behaviors during caregiver-infant interactions are measured inconsistently or are entirely absent from global assessment tools and coding schemes that assess quality of interactions. This lack of focus on physical interactive behaviors in assessments has led to a dearth of empirical evidence to support the theoretical importance of physical interaction between dyads. To support measurement of physical behaviors in the caregiver-infant interaction, we present a descriptive review of empirically-based global tools and coding schemes that do include a caregiver’s physical behaviors in their assessments. We searched recently published literature and extracted global caregiver-infant interaction observational assessment tools and coding schemes. We then identified measurement items within tools and schemes that captured caregiver physical behaviors. We discovered 29 unique tools or coding schemes that assessed caregiver physical behaviors in isolation of other variables. We coded physical behaviors using a 3-level approach: Physical Behavior, Functional Intention of Physical Interaction, and Qualitative Descriptors. Finally, we summarized validity and reliability evidence for these 29 tools to aid researchers and clinicians in selecting tools that explicitly include caregiver physical behaviors. We found that tools which assess a greater number of caregiver physical behaviors tend to have had more psychometric study than tools assessing fewer. We suggest that measuring caregivers’ physical behaviors during interactions with their infant may yield a more valid global assessment and should be considered a salient aspect of dyadic assessment. [Display omitted] •Global tools inclusive of caregiver physical interactive behaviors were reviewed.•Physical behavior is absent from many global tools that assess dyadic interaction.•When included in global tools, physical behaviors are inconsistently measured.•A method for consideration of physical behaviors during interaction is offered.•This review may guide selection of global tools inclusive of physical behavior.